PENGARUH JENIS WARNA DAN KETINGGIAN PERANGKAP TERHADAP SERANGAN SERANGGA PADA TANAMAN KENTANG (Solanum tuberosum L.) - Rama Adi Pratama, Novriza Sativa, dan Kamaludin (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2021)
This study aims to determine whether there is an interaction of the influence of color and trap height and the best combination of color response and trap height to pest attacks on potatoes. The study was conducted in Cintanagara Village, Cigedug District, Garut Regency from April to June 2020. The study used a randomized block design (RBD) with 2 factors and two replications. The first factor is color (w) which consists of four levels, namely w1 = yellow, w2 = green, w3 = red and w4 = blue. The second factor is height (p) which consists of four levels, namely p1 = 50 cm, p2 = 100 cm, p3 = 150 cm, and p4 = 200 cm. The results showed that there was an interaction between the coloration and the height of the trap against the pest attack on potato plants in the 2nd week of the pest population. The results showed that the insects found in potato (Solanum tuberosum L.) consisted of 7 types and 3 insect orders with the highest catch occurred at week 7 as many as 759 insects at 680 insect color at insect height in all traps. The combination of color types and trap heights at the w1 and p1 levels as well as the w2 and p1 levels gave the best results on the intensity of attack on potato plants. Coloring and trapping height at w1 and p1 levels gave the best results against the pest population on potato plants.